PARTISIPASI MASYARAKAT DESA DALAM PENYUSUNAN APBDES DI DESA MERTANI KECAMATAN KARANGGENENG KABUPATEN LAMONGAN - Heru Irianto; Tri Prasetijowati; Robichah Miladiyah (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2023)
The purpose of this research to describe the participation of village communities in the preparation of APBDes in Mertani Village, Karanggeneng District, Lamongan Regency. The type of research used is descriptive method with a qualitative approach and the data analysis used in this study is data collection, data reduction, data presentation, and drawing conclusions. Data collection techniques with in-depth interviews, documentation, and library studies. The informants in this study consisted of 6 (six) people who were considered to be able to provide detailed information on community participation in the preparation of the village income and expenditure budget. Through the results of research conducted by researchers using the theory of Cohen and Uphoff, it shows that community participation in the preparation of the village income budget, namely: (1) Participation in decision making, the community is involved in the preparation of the APBDes by expressing their opinions, conveying ideas and ideas, and also the village government considering even programs that are planned to be carried out by the village government are discussed once a year at the village development planning meeting (2) Participation in implementation, the existence of a mutual cooperation attitude of the village community in implementing the APBDes program (3) Participation in taking benefits, the village government using self-management that utilizes Mertani Village community. (4) Participation in the evaluation, the community is still less involved. Keywords: Participation, Society, APBDes